Numerical study on orthometric heights using a synthetic Earth gravity model - Fellner, Johannes Josef (Curtin University, 2011)
The fundamental problem of orthometric heights is that the mean gravity value cannot be determined due to the lack of precise topographical mass information. This thesis employs a global synthetic Earth gravity model, based on known and simulated global masses, in order to circumvent this problem. Applying forward gravity modelling techniques, the behaviour of gravity inside the topography as well as orthometric heights are studied in detail.